Comparative assessment of plasticity, stability and homeostasis based on ‘1000 grain weight’ in winter rye cultivars developed at VIR - N. I. Aniskov; I. V. Safonova (Труды по прикладной ботанике, генетике и селекции)
Background. In Russia, winter rye is a crop that provides food for people and feed for animals. Despite the obvious advantages of rye (high winter hardiness and drought resistance, plus the ability to grow in areas with poor soils and adverse climatic conditions), its area of cultivation has been reduced from 29 million hectares in 1913 to 872,000 ha in 2019. This situation can be improved by introducing rye cultivars with a stable yield of large grain under diverse growing conditions into commercial production.Materials and methods. The experimental part of the work was carried out in 2012–2017, in the experimental fields of Pushkin and Pavlovsk Laboratories of VIR. The target material was the accessions of low-pentosan winter rye cultivars developed at VIR. Data processing was performed using the analysis of variance according to B. A. Dospekhov. Adaptability and stability levels were calculated using the methods by S. A. Eberhart, W. A. Russell and L. A. Zhivotkov, those of plasticity and stability using the technique by G. C. Tai, the multiplicativity coefficient according to V. A. Dragavtsev, and the coefficient of homeostasis according to V. V. Hangildin, on the basis of ‘1000 grain weight’.Results and conclusion. The 1000 grain weight in the studied accessions varied from 30.0 to 48.2 g, with the average value of 40.8 g. The effect of the ‘test year’ factor on grain size was estimated at 65.5%, and of the ‘cultivar’ factor at 20.1%. The best conditions for large grain development were observed in 2013, 2015 and 2017 (45.7, 42.5 and 41.3 g, respectively). The most plastic, stable and homeostatic winter rye accessions were: Rushnik 2 (k-11820), ‘Krasnoyarskaya universalnaya’ (k-11818), ‘Bereginya’ (k-11822), Nika 3 (k-11823), and ‘Novaya Era’ (k-11814). The cultivars Rushnik 2, Nika 3, ‘Krasnoyarskaya universalnaya’, ‘Bereginya’ and ‘Novaya Era’ demonstrated high adaptability and can produce large grain under a wide range of varying environmental conditions.